Compliance of Hypertensive Patients with Medications at Marjan Teaching Hospital in Babylon Governorate - Nibras.H. Abdel-Hussein1, Gossoon J. Elywy2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hypertension is a significant problem around the world. As indicated by World Health Organization. Objectives: The aims of this study was to assess the compliance of hypertensive adults with their treatment, and to assess their socio-demographic characteristics in relation to compliance. Methodology: The study was conducted at the medical outpatients’ clinic in a period from 1st November 2018 to 10th march 2019 Marjan Teaching Hospital. Collecting data from simple random sampling total of (50) hypertensive patients who are using antihypertensive treatment and attending the medical outpatients’ clinic at Marjan Teaching Hospital in Babylon Governorate. Results: The majority of the study participants were female who accounted for (64%) of the total participants while male constituted (36%). Most of the study participants (42%) were between ages 60 years old more. Most of the respondents (63%) were diagnosed more than five years ago. (44%) of the sample have poor level of compliance with medications, and (50%) had poor control of blood pressure. Conclusions: There is very low rate of medication compliance, and BP control with strong association between them, that reinforce the relation between them.